Consumers’ awareness and knowledge of nanofood in Malaysia / Nor Akhmal Hasmin … [et al.] - Hasmin, Nor Akhmal; Mahmood, Anida; Azizun, Najwa; Abd Kadir, Nur Hafidah; Matmin, Juan (UiTM Press, 2021)
The integration of engineered nanomaterials (ENMs) in the food and agriculture industry is now common and rampant among giant food manufacturers to enhance the quality, functionality, and physicality of food products. However, consumers have not been consulted and informed on the use of ENMs in food despite various potential safety and health risks associated with oral exposure of ENMs illustrated from scientific studies. In the European Union, the food law was amended to include provisions on nanotechnology after conducting a public consultation to explore public awareness and perception of nanotechnology. In the absence of a specific regulatory framework for nanofood in Malaysia, this study aims to analyse consumers’ awareness and knowledge of nanofood. The result from the study serves as an invaluable input to the regulatory authority in framing any regulatory reform to regulate nanofood. A survey was conducted using a closed-ended questionnaire distributed online. The result indicates that the awareness and understanding of nanofood are still lacking and not satisfactory.